Offspring exposure to Crohn's disease during pregnancy and association with milder psychiatric regulatory disturbances in childhood - Skott, Elin; Söderberg, Gustav; Giacobini, MaiBritt; Nivins, Samson; Chen, Xinxia; Lindqvist, Daniel; Gissler, Mika; Sjöberg, Klas; Lavebratt, Catharina (John Wiley & Sons, 2025)
Introduction
Prenatal exposure to inflammatory states has been suggested to influence offspring neurodevelopment. The aim was to investigate if offspring exposure to maternal Inflammatory bowel disorder (IBD), or specifically the IBD disorder Crohn's disease, during gestation is associated with neurodevelopmental or psychiatric disorders in childhood.
Material and Methods
We conducted a population-based registry study in Finland. All live births from 1996 until 2014 in Finland were included and followed up until December 2018. Exposure was maternal IBD or Crohn's disease. Outcome was a broad range of neurodevelopmental and psychiatric disorders in offspring. Cox proportional hazards regression was applied to assess association. Sensitivity analyses included assessing, for example, exposure to severe episode of IBD or Crohn's disease, the outcome psychotropic medication for the children, and influence from perinatal risk factors.
Results
Of the participants (N = 1 105 997), 0.55% (N = 6067) were exposed to maternal IBD 0.18% (N = 1959) to maternal Crohn's disease. Among the children exposed to IBD or the subgroup Crohn's disease, 6.3% or 7.3%, respectively, had received an outcome diagnosis during the follow-up. There were higher risks for Sleeping disorders HR = 1.77 (95% CI, 1.13–2.78), Other feeding disorders HR = 1.83 (95% CI, 1.19, 2.19), and Incontinence HR = 1.42 (95% CI, 1.02–1.97) in children exposed to maternal Crohn's disease compared to unexposed children. This was supported by even higher point risk estimates for Incontinence HR = 2.43 (95% CI, 1.34–4.38) and Other feeding disorders HR = 2.83 (95% CI, 1.35–5.91) in offspring where the mother was hospitalized for Crohn's disease during pregnancy. Furthermore, there was a higher risk of dispensed antipsychotic, anxiolytic, hypnotic, and/or sedative medications for children with maternal Crohn's disease HR = 1.38 (95% CI, 1.03–1.85). These associations were not explained by cesarean section, preterm birth, or small birth size.
Conclusions
Offspring exposed to maternal Crohn's disease during pregnancy had modestly higher risks of early sleeping, continence, and feeding disturbances. The exposure had no detectable association with any of the other psychiatric disorders studied.